Combining ability of spring barley varieties in the direct diallel cross system - E. V. Kompanets; M. R. Kozachenko; N. I. Vasko; A. G. Naumov; P. N. Solonechniy; S. I. Sviatchenko (Вавиловский журнал генетики и селекции)
It is necessary to know the combining ability of starting material for effective breeding to create varieties. The research aim was to determine the peculiarities of the general combining ability (GCA) and specific combining ability (SCA) and the ratio of their variances for awned and awnless varieties and their parental forms in F1. The study was conducted in 2014–2015. Spring barley varieties and their parental forms were used in direct diallel crosses. In 2014–2015, peculiarities of the combining ability of awned and awnless spring barley varieties and their parental forms were determined in F1. We highlighted varieties with strong GCA effects: ‘Badioryy’ for plant productivity; ‘Dzherelo’, ‘Badioryy’, ‘Vitrazh’ and ‘Maliovnychyy’ for grain number per spike; ‘Dzherelo’, ‘Badioryy’, ‘Etiket’, ‘Granal’, ‘Modern’, ‘Vitrazh’, and ‘Tolar’ for 1000-grain weight; ‘Dzherelo’, ‘Granal’, and ‘Vitrazh’ for spike length; ‘Dzherelo’ and ‘Maliovnychyy’ for spikelet number per spike; ‘Dzherelo’, ‘Badioryy’ and ‘Granal’ for plant height; ‘Zvershennya’ and ‘Badioryy’ for productive tillering; ‘Zvershennya’ and ‘Badioryy’ for total tillering; and ‘Badioryy’ for straw weight. These varieties had the largest numbers of genes that positively determine these traits. The level of combining ability of parental forms may be manifested differently in varieties created via hybridization of them. GCA variances exceeded SCA variances in ‘Zvershennya’ in 2014–2015 for the trait “1000-grain weight” (GCA – 4.20 and 4.03, respectively; SCA – 3.78 and 3.84, respectively), therefore, it is determined mainly by additive gene effects. Strong and weak SCA effects were observed for plant productivity (grain weight) and its structural components (productive tillering, grain number per spike, 1000-grain weight). Strong SCA effects were the most numerous for the trait “1000-grain weight.”